2022
DOI: 10.3389/fenvs.2022.964698
|View full text |Cite
|
Sign up to set email alerts
|

Does phosphogypsum application affect salts, nutrients, and trace elements displacement from saline soils?

Abstract: Salinity and sodicity are the most agricultural challenges in arid and semi-arid regions. A pot experiment was undertaken, to evaluate the effect of Phosphogypsum (PG) and Gypsum (G), to remove salts, nutrients and trace elements in leached water from saline and saline-sodic soils. In order to determine the efficiency and safety of these amendments, as an affordable strategy, for overcoming salinity and sodicity stress. The PG at 0, 15, 30 and 45 t/ha and G at 15 t/ha were mixed with the upper 9 cm soil in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Indeed, K and Mg contents could not affect the amendment application. On the other hand, several authors reported that G and PG applications increased K and Mg leaching from the soil [71,72]. He et al reported that Ca: Mg ratios did not influence clay dispersion of montmorillonite and kaolinite [73].…”
Section: Effect Of Amendment By Phosphogypsum/gypsum On Soil-aggregat...mentioning
confidence: 99%
“…Indeed, K and Mg contents could not affect the amendment application. On the other hand, several authors reported that G and PG applications increased K and Mg leaching from the soil [71,72]. He et al reported that Ca: Mg ratios did not influence clay dispersion of montmorillonite and kaolinite [73].…”
Section: Effect Of Amendment By Phosphogypsum/gypsum On Soil-aggregat...mentioning
confidence: 99%
“…Phosphogypsum is a low-cost co-product of the phosphoric acid industry, which is produced in several African countries such as Morocco, Tunisia, South Africa, Egypt, and Senegal [6][7][8][9][10][11] . Phosphogypsum finds extensive application in agriculture as an amendment for depleted soils (including saline, sodic, alkaline, and acidic) and as a fertilizer 12 . Phosphogypsum contains a variety of essential nutrients crucial for plant growth and development, such as calcium (Ca), sulfur (S) and phosphorus (P).…”
Section: Introductionmentioning
confidence: 99%
“…The utilization of PG in agriculture as an amendment has become a topic of considerable interest, not only because of its potential benefits but also because of concerns regarding its handling, storage, and recycling. For instance, PG has been widely used to ameliorate physical and chemical properties of degraded soils, including salinesodic soils (Outbakat et al, 2022) and acid soils (Bouray et al, 2022). Phosphogypsum contains soluble and insoluble elements and impurities.…”
Section: Introductionmentioning
confidence: 99%